PLASMA CELL LEUKEMIA - Đurđević, Predrag; Jovanović, Danijela (Srpski medicinski časopis Lekarske komore, 2025)
Plasma cell leukemia (i.e., plasmacytic leukemia) is a very rare and aggressive form of plasma cell dyscrasia characterized by a poor prognosis, short survival time, and a poor response to the administered therapy. Clinical manifestations vary, however, the extramedullary form of the disease is the most common, as are hypercalcemia, anemia, thrombocytopenia, impaired renal function, and increased lactate dehydrogenase concentration. Numerous cytogenetic abnormalities lead to greater proliferation, inhibition of apoptosis, and changes in the expression of adhesion molecules and chemokine receptors. Despite the introduction of new therapeutic modalities based on bortezomib, immunomodulatory drugs, and biological therapy, the therapeutic outcome is still unsatisfactory.